The tithe in the Gospel and Nigerian Christians’ notion: an analysis and description study - Obalowu, Issah Abeebllahi; Abdul Rahim, Adibah (Kulliyyah of Islamic Revealed Knowledge and Human Sciences (KIRKHS), International Islamic University Malaysia, 2019)
The worldview of Nigerian Christians about the monthly tithing to their local churches is well known to the public, as they believe in its obligation upon every Christian. However, the belief that resulted from the local churches leaders’ preaching had been a dogma in the midst of Nigerian Christians. Recently, a Nigerian radio host and presenter, popularly known as Daddy Freeze came up with an idea of refuting offering tithe to the local churches, claiming that the act of offering tithe to them is contrary to Christ’s teaching in the New Testament. He as well considered the act of tithing as a modern way of scam by those pastors. The move has created a kind of uproar and confusion within the Nigerian Christians community and led to different reactions from many renowned Nigerian pastors and evangelists. Thus, this research aims at studying the Tithe within the paradigm of the New and Old Testament; definition and origin of the tithe, what is to be given as a tithe and when, who is to give the tithe and to whom is to be given? All these issues will be discussed according to the Bible and Christians worldview.